2015
DOI: 10.1007/s11999-014-4116-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite-coated Collars Reduce Radiolucent Line Progression in Cemented Distal Femoral Bone Tumor Implants

Abstract: Background Aseptic loosening of massive bone tumor implants is a major cause of prosthesis failure. Evidence suggests that an osteointegrated hydroxyapatite (HA)-coated collar would reduce the incidence of aseptic loosening around the cemented intramedullary stem in distal femoral bone tumor prostheses. Because these implants often are used in young patients with a tumor, such treatment might extend the longevity of tumor implants. Questions/purposes We asked whether (1) HA-coated collars were more likely to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…Recent radiographic and histological study investigating bone ingrowth into a HA collar in the distal femoral implants used to treat patients of all ages showed increased survivorship and reduced radiolucent line progression when osseointegration at the shoulder could be identified compared to implants where ingrowth was not evident [24,37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent radiographic and histological study investigating bone ingrowth into a HA collar in the distal femoral implants used to treat patients of all ages showed increased survivorship and reduced radiolucent line progression when osseointegration at the shoulder could be identified compared to implants where ingrowth was not evident [24,37].…”
Section: Discussionmentioning
confidence: 99%
“…Managing aseptic loosening of SAAP due to periprosthetic bone resorption is key to clinical success, as studies using similar endoprostheses have shown. 4,8,9 Endosteal resorption will destabilise the implant, conversely if osseointegration and bone growth into the collar can be achieved without radiolucency, then the implant will be stabilised. 8,15 The damage repair theory suggests that when damage from fatigue or impact occur, bone can detect, remove and replace it within resorption cavities.…”
Section: Implant Stem Material Sed and Bone Remodellingmentioning
confidence: 99%
“… Study Reason for exclusion No. Study Reason for exclusion 1 Singh A et al., 2014 [34] Only one patient 17 Cook DC et al., 2013 [35] Not comparing a synthetic bone substitute 2 Coathup MJ et al., 2015 [36] Treatment not for alveolar bone 18 Menezes LM et al., 2012 [37] Not comparing a synthetic bone substitute 3 Kato E et al., 2015 [38] Outcome measure not related to alveolar bone regeneration 19 Horvarth A et al., 2013 [39] Not comparing a synthetic bone substitute 4 Gupta G et al., 2014 [40] Not comparing a synthetic bone substitute 20 Ghanaati S et al., 2013 [25] Control group not available 5 Troedan A et al., 2014 [41] Outcome measure not related to alveolar bone regeneration 21 Pietruska M et al., 2012 [42] Outcome measure not related to alveolar bone regeneration 6 Reichert C et al., 2014 [43] Outcome measure not related to alveolar bone regeneration 22 Emam H et al., 2011 [44] Not comparing a synthetic bone substitute and control group not available 7 Cosso MG et al., 2014 [3] Not comparing a synthetic bone substitute 23 Lee CY et al., 2011 [45] Not comparing a synthetic bone substitute 8 Ghanaati S et al., 2014 [46] Outcome measure not related to alveolar bone regeneration 24 Mairoana C et al., 2011 [47] …”
Section: Resultsmentioning
confidence: 99%